(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze critical thinking skills based on the SOLO Taxonomy in junior high school students with high, medium, and low learning independence categories. The type of research used is qualitative descriptive. The subjects of this study are eighth-grade students of SMP Negeri 1 Maduran. The data collection techniques used are questionnaires, tests, and interviews. Data analysis is conducted qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The research results conclude that students with high learning independence are able to meet all indicators of critical thinking skills and all 3 levels of the SOLO taxonomy. Students with moderate learning independence are able to meet 4 indicators of critical thinking skills and 2 levels of the SOLO taxonomy. Students with low learning independence can only meet 2 indicators of critical thinking skills and 1 level of the SOLO taxonomy.